2020
DOI: 10.1038/s41408-019-0270-0
|View full text |Cite
|
Sign up to set email alerts
|

A new regulatory mechanism of protein phosphatase 2A activity via SET in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is an aggressive hematologic malignancy. Although novel emerging drugs are available, the overall prognosis remains poor and new therapeutic approaches are required. PP2A phosphatase is a key regulator of cell homeostasis and is recurrently inactivated in AML. The anticancer activity of several PP2A-activating drugs (e.g., FTY720) depends on their interaction with the SET oncoprotein, an endogenous PP2A inhibitor that is overexpressed in 30% of AML cases. Elucidation of SET regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…We have also demonstrated that similar mechanisms of CK2-mediated PTEN inactivation exist in B-ALL and CLL and are of relevance for leukemia cell maintenance [12,47,49]. Moreover, CK2 is relevant in biology, and resistance to therapy, of acute myeloid leukemia (AML) and chronic myeloid leukemia (CML) [11,[50][51][52][53]. Thus, there is a clear rationale to explore the use of CK2 inhibitors in the clinical setting in different leukemias, including T-ALL.…”
Section: Discussionmentioning
confidence: 80%
“…We have also demonstrated that similar mechanisms of CK2-mediated PTEN inactivation exist in B-ALL and CLL and are of relevance for leukemia cell maintenance [12,47,49]. Moreover, CK2 is relevant in biology, and resistance to therapy, of acute myeloid leukemia (AML) and chronic myeloid leukemia (CML) [11,[50][51][52][53]. Thus, there is a clear rationale to explore the use of CK2 inhibitors in the clinical setting in different leukemias, including T-ALL.…”
Section: Discussionmentioning
confidence: 80%
“…This could be due to the higher p38α expression in most cell types, but might also reflect that p38α can perform particular functions, as suggested by the inability of p38β expressed under control of the p38α endogenous promoter to rescue p38α phenotypes in mice 21 . Nevertheless, experiments with cell cultures have identified some functions that can be mostly performed by p38β 22 . In addition, some cells may rely on p38β as a backup for p38α, as shown by the additional phenotypes observed in mice in which genes encoding both p38α and p38β were knocked out, compared with the single knockouts.…”
Section: P38 Kinase Family Membersmentioning
confidence: 99%
“…Treatment of engrafted leukemic blasts from patient 4 reflected the poor response during the treatment coarse. Zebrafish have received more attention during the last decade as an embryonic model host for xenografts, with nine publications exploring engraftment of other leukemic blast cell types to date [21,24,25,36,[38][39][40][41]. The ALL-ZeFiX assay both provides proof-of-principle for BCP-ALL exgraftment and extends the clinical utility of drug testing in immunosuppressed zebrafish avatars with quantifiable endpoint analysis and a 5-day assay format.…”
Section: Discussionmentioning
confidence: 99%